2018
DOI: 10.1016/j.ijcha.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Invasive physiological indices to determine the functional significance of coronary stenosis

Abstract: Physiological measurements are now commonly used to assess coronary lesions in the cardiac catheterisation laboratory, and this practice is evidence-based and supported by clinical guidelines. Fractional flow reserve is currently the gold standard method to determine whether coronary lesions are functionally significant, and is used to guide revascularization. There are however several other physiological measurements that have been proposed as alternatives to the fractional flow reserve. This review aims to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Overall, using invasive physiological coronary blood flow indices to assess lesion functional significance improves clinical outcomes in patients with MV CAD [ 25 ] and in patients with non-culprit coronary lesions during the acute phase [ 26 , 27 ]. FFR has been widely investigated, and after obtaining significant data regarding a reduction in the composite endpoint, which includes death, MI, and repeat revascularization, in the Fractional Flow Reserve versus Angiography for Multivessel Evaluation (FAME) study, evidence on the utility of FFR for the management of patients with ACS began to emerge [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, using invasive physiological coronary blood flow indices to assess lesion functional significance improves clinical outcomes in patients with MV CAD [ 25 ] and in patients with non-culprit coronary lesions during the acute phase [ 26 , 27 ]. FFR has been widely investigated, and after obtaining significant data regarding a reduction in the composite endpoint, which includes death, MI, and repeat revascularization, in the Fractional Flow Reserve versus Angiography for Multivessel Evaluation (FAME) study, evidence on the utility of FFR for the management of patients with ACS began to emerge [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the previously reported diagnostic agreement between FFR and HSR in the general population of 78.7% ( 30 ). However, HSR is also dependent on an adequate hyperaemic response, and can be confounded by the presence of microvascular dysfunction ( 13 ). Previously, Kochiadakis et al indicated that irregularities in ventricular rhythm may be responsible of diminished CFR in AF ( 10 ), while a recent case report by Mills et al highlighted that changes in cardiac rhythm associated with AF may impact coronary physiological assessment ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic measurements were performed under basal conditions and under hyperaemia induced by intracoronary administration of adenosine (dose of 150 μg, increased progressively until attaining maximal hyperaemia). CFR is calculated as the ratio of maximum blood flow during hyperaemia (hAPV—hyperaemic average peak velocities) and resting coronary blood flow (bAPV—baseline average peak velocities), and reflects both the epicardial and the microcirculatory coronary status ( 13 ). Given the irregular RR interval in AF with potential impact on coronary flow, APV was calculated as the average instantaneous peak velocity over an interval of 5 beats.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This clinical diagnostic score system may help to prescreen for coronary artery spasm in patients with acute chest pain. Additionally, several invasive and non-invasive strategies are currently used to assess the functional significance of coronary lesions [46], [47] and coronary CT angiography is a widely used strategy to detect significant coronary lesions non-invasively [48], [49].…”
Section: Coronary Artery Disease and Myocardial Infarctionmentioning
confidence: 99%